Structure and Composition of the Understory Vegetation in Bunder Wonosari Grand Forest Park, Gunung Kidul Regency, Yogyakarta Province - Gare, Kletus Florianus Sera; Rusadi, Nusrah; Selanno, Frenly Marvi; Syah, Firman; Silaban, Rosalia; Lamanda, Sukriati Andesti; Marpaung, Sutan Sahala Muda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bunder Grand Forest Park (Tahura) is a nature conservation area that plays a crucial role in maintaining the sustainability of biological resources and ecosystems in the Yogyakarta region. The development of Bunder Grand Forest Park is not only focused on ecological preservation but also contributes to strengthening Yogyakarta's identity as a center for environmentally conscious education and tourism. This study aims to determine the types of undergrowth, INP and its species diversity. This study was conducted using a quadrat sampling technique, using a double plot method. For observations used PU with a size of 1 m x 1 m. The results of research conducted in the Bunder Forest Park area, found 21 types of undergrowth, which are divided into 2 groups, namely non-grass plants and grass-type undergrowth, with the largest INP value obtained by the type of non-grass plant, namely the Bandotan plant (Ageratum conyzoides L.), with a value of 43.22%, and the grass-type undergrowth, namely the Elephant grass plant (Pennisetum purpuroides) with a value of 84.39% while the undergrowth with the lowest INP value, obtained by the type of non-grass plant, namely Lamtoro (Leucaena leucocephala), with a value of 3.15%, and the grass-type plant, namely the Grepak Grass plant (Paspalum conjugatum Berg.) with a value of 6.57%. In terms of diversity, non-grass understory plants are known to have moderate species diversity, while grass understory plants have low species diversity.